Non-traumatic Fatalities in Football: Over-conditioning Kills. Issue 7 (29th July 2019) - Boden, Barry P.; Breit, Ilan; Anderson, Scott
Objectives: Football is associated with the highest number of fatalities of any high school (HS) or college sport. In contrast to the annual number of traumatic fatalities in football, which has declined 4-fold since the 1960's, the annual number of non-traumatic fatalities has stayed constant with current rates that are 2 to 3 times higher than traumatic fatalities. The purpose of this study was to describe the epidemiology and causes of non-traumatic fatalities in HS and college football players, to determine the effectiveness of the NCAA policies to reduce heat and sickle cell trait (SCT) fatalities, and to provide prevention strategies. Methods: We retrospectively reviewed non-traumatic football fatalities identified over a 20 year period from July 1998 through June 2018. Information was obtained from extensive internet searches, as well as depositions, investigative, autopsy, media, and freedom of information reports. Heat and SCT fatality rates were compared pre and post implementation of the NCAA football acclimatization model (2003) and SCT screening (2010) policies, respectively. Results: There were 187 (150 H.S., 37 college) non-traumatic fatalities (avg. 9/yr.). The most common causes of fatalities were cardiac (98, 52%), heat (44, 24%), SCT (23, 12%), and asthma (10, 5%). The majority of fatalities (127, 68%) occurred outside of the regular season months of September through December with the most common month for fatalities being August (61, 33%). Most (163, 87%) of the fatalities occurred during a practice or conditioning session (heat=100%, SCT=100%, asthma=90%, cardiac=77%). Hallmarks of exertion-related fatalities were: 1. conditioning sessions supervised by the football coach or strength and conditioning coach, 2. irrationally intense workouts and/or punishment drills, and 3. an inadequate medical response. The average annual rate of heat-related fatalities remained unchanged at the collegiate level pre (0.4) and post (0.4) implementation of the NCAA football acclimatization model in 2003. The average annual number of SCT deaths in collegiate football declined 58% (0.83 to 0.25) after the 2010 NCAA SCT screening policies were implemented. At the HS level, where there are no SCT guidelines, the number of SCT fatalities increased 400% (0.25/yr. to 1.0/yr.) since 2010. Conclusion: Most non-traumatic fatalities in HS and college football athletes do not occur while playing the game of football, but rather during conditioning sessions which are often associated with overexertion and/or punishment drills by coaches, especially strength and conditioning coaches. The football acclimatization model implemented by the NCAA in 2003 has failed at reducing exertional heat-related fatalities at the collegiate level. SCT screening policies adopted by the NCAA in 2010 have been effective at reducing fatalities in college athletes and similar guidelines should be mandated at the HS level. Conditioning related fatalities are preventable by establishing standards in workout design, holding coaches and strength and conditioning coaches accountable, ensuring compliance with current policies, and allowing athletic health care providers complete authority over medical decisions.